Does crystallographic anisotropy prevent the conventional treatment of aqueous mineral reactivity? A case study based on K-feldspar dissolution kinetics. (1st October 2016) - Pollet-Villard, Marion; Daval, Damien; Ackerer, Philippe; Saldi, Giuseppe D.; Wild, Bastien; Knauss, Kevin G.; Fritz, Bertrand
Abstract: Which conceptual framework should be preferred to develop mineral dissolution rate laws, and how the aqueous mineral reactivity should be measured? For over 30 years, the classical strategy to model solid dissolution over large space and time scales has relied on so-called kinetic rate laws derived from powder dissolution experiments. In the present study, we provide detailed investigations of the dissolution kinetics of K-feldspar as a function of surface orientation and chemical affinity which question the commonplace belief that elementary mechanisms and resulting rate laws can be retrieved from conventional powder dissolution experiments. Nanometer-scale surface measurements evidenced that K-feldspar dissolution is an anisotropic process, where the face-specific dissolution rate satisfactorily agrees with the periodic bond chain (PBC) theory. The chemical affinity of the reaction was shown to impact differently the various faces of a single crystal, controlling the spontaneous nucleation of etch pits which, in turn, drive the dissolution process. These results were used to develop a simple numerical model which revealed that single crystal dissolution rates vary with reaction progress. Overall, these results cast doubt on the conventional protocol which is used to measure mineral dissolution rates and develop kinetic rate laws, because mineral reactivity is intimately related to the morphology of dissolving crystals, which remains totally uncontrolled in powder dissolution experiments. Beyond offering an interpretive framework to understand the large discrepancies consistently reported between sources and across space scales, the recognition of the anisotropy of crystal reactivity challenges the classical approach for modeling dissolution and weathering, and may be drawn upon to develop alternative treatments of aqueous mineral reactivity.